Energy Dissipation and Fractal Properties of Coal under Cyclic Impact Loading - Yongliang He; Chuantian Li; Yuping Fu; Xuegang Xing; Liying Sun (Advances in Civil Engineering)
To investigate the periodic disturbance and damage characteristics of coal under different impact pressures, the stress‒strain failure and damage trends of weak, impact-prone coal samples were analysed under different impact pressures and different numbers of impacts. Split-Hopkinson pressure bar (SHPB) tests were conducted to study the stress‒strain curve, dynamic compressive strength, elastic modulus, failure strain, and absorbed energy responses with different numbers of impacts and different strain rates. Fractal theory and methods were applied to analyse the influence of different impact pressures and different numbers of impacts on coal sample failure to reveal the relationship between the number of impacts and the fractal size characteristics of coal fragmentation. The energy modes and failure modes of coal samples under different impact effects were analysed under dynamic loading. Regarding the energy absorption corresponding to different numbers of impacts, the energy absorption per unit volume (EAPUV) of three impacts was calculated to be 0.46 J/cm3. The number of impacts was directly correlated with the energy absorbed by the coal sample. Furthermore, the number of impacts was directly correlated with the severity of the deformation and damage of the coal sample and was inversely correlated with the fragmentation of the coal sample. The degree of coal sample fragmentation was directly proportional to the number of impacts, and the fractal dimension increased with the number of impacts. The study of the failure and fractal characteristics of coal samples under different impact pressures and different numbers of impacts provides important information for the prevention and control of coal mine rock bursts.